Ahmad Yasavï héros des nouvelles républiques centrasiatiques - Thierry Zarcone (Revue des Mondes Musulmans et de la Méditerranée)
This study deals with the re-reading of the writings — mosly poetry — attributed to the 11th century famous Sufi Ahmad Yasavi by the intellectuals, politicians and journalists of the present Central Asian Republics of the former SSSR. There is first a presentation of Ahmad Yasavi's writings who have left an imprint in both popular and literary spheres of Central Asia, including the Volga area and Eastern Turkestan. My opinion is that since the 11th century, Ahmad Yasavi became a myth in Central Asia because of the lack of reliable documents about his real thinking. For that reason, the interpretation of his thought by the Muslims — both enlightened and conservatists — by the Marxist and by the present intellectuals and politicians of the new Republics has led to variative and contradictory interpretations. This paper attempts to analyse these interpretations in relation with Central Asian culture and society and to explain how Ahmad Yasavi's writings inspired the Muslim modernists (jadid) of the 19th-20th centuries who have depicted him as a nationalist, proletarian and socialist poet, and why during the SSSR, after the assassination by Stalin of the last jadid, he was on the contrary, considered as a feodalist, a bourgeois and an apostle of the reactionary dogma, in a sense a « cursed saint ». The last part of this article focuses in a contemporary period and analyses how Ahmad Yasavi's myth has been interpreted since 1991, in relation with the process of shaping the new identity of the Central Asia and the re-building of Islam. As a result of the contemporary re-reading, one can notice that Ahmad Yasavi is becoming the model of the perfect Central Asian citizen. In brief, exaggerated mysticism has been evacuated and only nationalistic and religiously open-minded dispositions of Ahmad Yasavi have been welcomed in order to fit to the new social and religious conditions of the new Central Asian society. But in several cases interpretation means distortion.